Kemampuan Koneksi Matematik Siswa dalam Menyelesaikan Soal Investigasi Matematika - Ade Irawan; Sri Subarinah; Arjudin Arjudin; Sudi Prayitno (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aims to determine and describe the level of mathematical connection ability of students in solving mathematical investigation questions in grade VII students at SMPN 2 Labuapi in the academic year 2020/2021. This type of research is descriptive qualitative research. The subjects in this study were 10 students of VII A class at SMPN 2 Labuapi. The data was collected in the form of test results of students' mathematical connection skills in solving mathematical investigation questions at triangles and quadrangle matter and the results of interviews. The test results were analyzed according to the indicators of students' mathematical connection ability, which is being able to connect the mathematical concepts that have been studied and those being studied and to connect the mathematical concepts to everyday life. Based on the results of data analysis, that the mathematical connection ability of students in solving mathematical investigation questions was still in the sufficient category. Overall there were 3 students (30%) in very poor category, 2 students (20%) in very good category, 2 students (20%) in good category, 2 students (20%) in good enough category, and 1 student (10%) in poor category.